PENERAPAN HUKUM ADAT PATI NYAWA DAYAK CUPANG DESA DILUAR WILAYAH BARU LOMBAK TERHADAP KORBAN KECELAKAAN DI KECAMATAN MELIAU - NIM. A1012211070, KERISTINA APRIYANTI (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract This study discusses the application of Pati Nyawa customary law in the Dayak Cupang community of Baru Lombak Village outside the customary law area towards accident victims in Singkawang City on Thursday, December 12, 2024, resulting in the death of one of the Dayak Cupang indigenous people. The fine for the perpetrator is in accordance with the provisions of the Dayak Cupang customary law book and according to the agreement between the two parties in exchange for the victim's life. The problem formulation in this study is How is the Application of the Customary Law